Rare Presentation of An OKC Involving The Ectopic Maxillary Third Molar in The Sinus and its Management - Merin John, Jestina; Byakodi, Sanjay; Tamboli, Abdulla; Menon, Vishnuchandra; Khan, Mushtak; Kale, Dhananjay (Journal of Neonatal Surgery, 2025)
Ectopic development of teeth in non-tooth bearing areas is uncommon, especially in the maxillary sinus. We report a case of a 27-year-old male patient who presented with purulent discharge posterior to the upper right second molar with a bad taste and foul odour. An orthopantomography is the routine diagnostic radiographic examination performed for this type of eruption, although cone beam computed tomography (CBCT) is highly recommended for further localization of the ectopic tooth and assessment of the characteristics of any associated lesion before a surgical procedure. Radiographic examination revealed right maxillary third molar tooth located at the posterosuperior aspect of the right maxillary sinus with a hyperdense lesion surrounding the crown, obliterating the sinus cavity. Both the tooth and infected odontogenic keratocyst were surgically removed under general anaesthesia through Caldwell-Luc antrostomy. After a one-month follow-up, the patient was symptom free and had an uneventful recovery. One of the most frequent conditions affecting the oral and maxillofacial areas are odontogenic cysts.